Preparation method and application of composite filler

By mixing high-dispersed silica with composite oxide catalyst and preparing composite fillers, the problems of insufficient uniformity and high cost of composite fillers in the prior art are solved, and the mechanical properties and preparation efficiency of rubber are significantly improved.

CN119875200APending Publication Date: 2025-04-25NINGBO ZHONGWU NEW MATERIAL IND TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510100695.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the existing rubber composite filler preparation methods, the insufficient uniformity of the composite filler and the high raw material cost lead to limited improvement in rubber performance.

Method used

By mixing high-dispersible silica with a composite oxide catalyst in a specific proportion and reacting under specific conditions, a composite filler combining high-dispersible silica and carbon nanotubes is prepared to improve its uniform distribution in the rubber.

Benefits of technology

The mechanical properties of rubber, such as tensile strength and fracture strain, are significantly improved, so that rubber products have better performance while reducing the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254112640000081
    Figure BDA0005254112640000081
  • Figure BDA0005254112640000091
    Figure BDA0005254112640000091
Patent Text Reader

Abstract

The invention provides a preparation method of a composite filler, which comprises the following steps: mixing high-dispersion silicon dioxide with a Fe2O3-MoO3-Al2O3 composite oxide catalyst, feeding into a reactor, and reacting at a specific temperature in a gas environment to obtain the composite filler; meanwhile, the invention also provides the composite filler obtained by the preparation method and application of the composite filler in preparation of rubber. In addition, the invention also discloses a preparation method of the rubber product, which comprises the following steps: putting the acrylonitrile-butadiene copolymer and other raw materials into a mixing mill, adding industrial zinc oxide, stearic acid and other auxiliary materials, stirring, adding the prepared composite filler and plasticizer, continuously stirring, finally adding the accelerant, uniformly stirring, standing, and vulcanizing at a certain temperature and pressure to obtain the rubber product. The rubber product is obtained. According to the method disclosed by the invention, the uniform distribution of the filler in the rubber is remarkably improved, the problem of non-uniform distribution of the filler in the prior art is solved, and the mechanical property of the rubber can be more remarkably improved under the condition of the same filler content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new materials, and in particular to a preparation method of a composite filler and application thereof. Background Art

[0002] In recent years, composite fillers have been widely used in rubber compositions to improve performance. These fillers include but are not limited to carbon nanomaterials (such as nanotubes, graphene nanoplates, graphene oxide nanoplates, carbon nanofibers) and highly dispersed silica (white carbon black).

[0003] In the prior art, a typical method for preparing a rubber composite filler is disclosed in patent CN107955224. The method prepares a rubber composite filler by the following steps: Ultrasonic treatment: The carbon nanotubes are dispersed in deionized water to which a dispersion modifier poly N-vinyl acetamide (PNVA) is added, and the carbon nanotubes are uniformly dispersed by ultrasonic treatment. Adding an affinity modifier: An affinity modifier (such as natural latex) is added to the above dispersion to promote the combination of the carbon nanotubes with other components. Flocculation and drying: The obtained dispersion is flocculated, washed and dried to obtain a preliminary product. Adding other components: Highly dispersed silica (white carbon black), silane coupling agent, activator and antioxidant are added to the preliminary product under stirring to obtain a final rubber composite filler.

[0004] However, this method has the following defects: 1. Insufficient uniformity of composite filler: Although the carbon nanotubes are uniformly dispersed by ultrasonic treatment, the addition of highly dispersed silica and other components in the subsequent steps may destroy the original uniform dispersion state, resulting in insufficient uniformity of the composite filler, which in turn affects the improvement of rubber performance. 2. High cost of raw materials: Using expensive carbon nanotubes and natural latex as raw materials makes the preparation process labor-intensive and time-consuming, with high costs, which is not conducive to large-scale production applications.

[0005] Another prior art is to introduce highly dispersed silica and multi-walled carbon nanotubes when melt blending nitrile rubber (acrylonitrile-butadiene copolymer) in a double-roll mill (MM Salehi, T. Khalkhali, and A. A. Davoodi; Polymer Science, Series A, 2016, Vol. 58, No. 4, pp. 567-577). Highly dispersed silica (white carbon black) and multi-walled carbon nanotubes are introduced when melt blending nitrile rubber (acrylonitrile-butadiene copolymer) in a double-roll mill, and the performance of the prepared rubber mixture based on acrylonitrile-butadiene copolymer (nitrile rubber) is studied. The results show that the simultaneous use of highly dispersed silica (white carbon black) and multi-walled carbon nanotubes has a synergistic effect. The degree of improvement in the performance of the prepared rubber mixture exceeds the expectation derived from the superposition theorem.

[0006] Although studies have shown that this method has a synergistic effect with the two reinforcing fillers and can significantly improve the performance of the rubber mixture, it also has the defect of uneven filler distribution: during the melt blending process, the distribution of highly dispersed silica and multi-walled carbon nanotubes in the rubber composition is not uniform enough, which limits the further improvement of the mechanical properties of the rubber. Summary of the invention

[0007] In order to solve the above problems, the present invention discloses a method for preparing a composite filler and its application. By changing the method parameters and introducing a new operating process, highly dispersed silica and a composite oxide catalyst are prepared in advance into a filler combined with highly dispersed silica and carbon nanotubes, and then the corresponding rubber products are prepared, thereby improving the uniformity of the distribution of highly dispersed silica and multi-walled carbon nanotubes in the rubber and enhancing the mechanical properties of the rubber prepared using the composite filler of the present invention.

[0008] The present invention includes the following technical solutions:

[0009] A method for preparing a composite filler comprises the following steps:

[0010] 1) mixing highly dispersed silicon dioxide and a composite oxide catalyst for preparing carbon nanotubes in a mass ratio of 1:1 to 85:1; the composite oxide catalyst is Fe2O3-MoO3-Al2O3, and its atomic ratio is Fe:Mo:Al=1:(0.04-0.21):(1-3);

[0011] 2) The mixed materials are fed into a reactor, and the mixed materials are sprayed into a mixed gas consisting of hydrogen, ethylene or propylene, and carrier gas argon at a temperature of 650°C-700°C to react;

[0012] 3) After the reaction is completed, the introduction of the mixed gas is stopped, the heating device is turned off, and the reactor is purged with argon to obtain a composite filler.

[0013] Furthermore, in the above-mentioned method for preparing a composite filler, the reaction time of the mixed material in step 2) in the reactor is 20-60 minutes.

[0014] Furthermore, in the above-mentioned method for preparing a composite filler, before the step 2) feeding the mixed materials into the reactor, the step also includes the step of stirring the mixed materials in a planetary mixer for 5-10 minutes.

[0015] Furthermore, in the above-mentioned method for preparing a composite filler, the reactor in step 2) is a cylindrical quartz reactor, which is driven by electricity to rotate at a speed of 60-90 rpm, and the rotation axis of the reactor is inclined at 8° to the horizontal plane.

[0016] Furthermore, in the above-mentioned method for preparing a composite filler, in step 2), during the reaction process, argon gas is first introduced to make the pressure in the reactor reach a predetermined value, and then the mixed material is sprayed into the reactor, and then the flow rate of argon gas is adjusted, and a mixed gas of hydrogen, ethylene or propylene is introduced.

[0017] Furthermore, in the above-mentioned method for preparing a composite filler, the predetermined value is 400-450cm 3 / min argon flow rate.

[0018] Furthermore, in the above-mentioned preparation method of a composite filler, during the reaction process, the flow rate of the mixed gas of hydrogen, ethylene or propylene is 400cm 3 / min, the flow rate of argon carrier gas was 400 cm 3 / min.

[0019] The invention also discloses a composite filler, which is prepared by the above-mentioned preparation method.

[0020] The invention also discloses the preparation method or the use of the composite filler in preparing rubber.

[0021] The present invention also discloses a rubber product, which is characterized by being prepared by the following steps:

[0022] a. Load 80-120 parts of acrylonitrile-butadiene copolymer NBR 3365 into a Banbury Z-type mixer, add 3-8 parts of industrial zinc oxide, 1-2 parts of stearic acid, 1-3 parts of IPPD antioxidant, 0.5-1.5 parts of internal release agent ASTM 935P and 0.03-0.08 parts of sulfur powder, and continue stirring for 4-6 minutes;

[0023] b. Add 1-5 parts of the prepared composite filler and 5-15 parts of plasticizer DOP, and continue stirring for 2-5 minutes;

[0024] c. Pour out the obtained mixture and cool it to below 110°C, then add 1-2 parts of accelerator CBS (N-cyclohexyl-2-benzothiazole sulfenamide) and 1-3 parts of accelerator (tetramethylthiuram disulfide) into an open double-roll mixer and stir until uniform;

[0025] d. Place the resulting mixture at room temperature for 12-36 hours and then vulcanize it at 140-160°C and a pressure of 12-18 MPa.

[0026] Compared with the prior art, the present invention has the following outstanding beneficial effects:

[0027] The present invention proposes a novel method for preparing a composite filler, by mixing highly dispersed silica with a composite oxide catalyst in a specific ratio and reacting under specific conditions, a composite filler combining highly dispersed silica and carbon nanotubes is successfully prepared. This composite filler can be evenly dispersed in rubber, significantly improving the mechanical properties of the rubber, such as tensile strength, fracture strain, etc., so that the rubber product has better performance. DETAILED DESCRIPTION

[0028] The method of the present invention is implemented as follows: highly dispersed silicon dioxide and a catalyst for preparing carbon nanotubes are poured into a Waring 8.8A012 planetary mixer and stirred for 5-10 minutes, with a mass ratio of 1:1 to 85:1. 3 A cylindrical quartz reactor can be driven by electricity to rotate at a speed of 60-90 rpm, so that highly dispersed silica and a catalyst for preparing carbon nanotubes are mixed in a mixed gas consisting of hydrogen, ethylene or propylene and carrier gas argon. The rotating axis of the reactor is inclined at 8° to the horizontal plane. The mixed gas is introduced into the reactor through a fixed quartz extension tube inlet, which is connected to the reactor neck through a ground joint lubricated with mineral oil. The reactor is placed in a temperature-controlled electric furnace and heated to 650-700°C. In an argon flow (400-450cm 3 / min), the mixture of the prepared highly dispersed silica and the catalyst for preparing carbon nanotubes is introduced into a reactor for synthesizing composite fillers heated to 650-700°C. Then the argon flow rate is reduced to 40-45 cm 3 / min. Hydrogen, ethylene or propylene (400cm 3 / min) and argon carrier gas (400cm 3 A mixed gas composed of argon and argon (g / min) was introduced into a reactor for synthesizing a composite filler. The gas flow rate was measured at room temperature. The exhaust gas mixture was discharged through a quartz exhaust pipe. After 20-60 minutes, the introduction of the mixed gas was stopped, the heating device was turned off, the reactor was purged with argon, and the obtained composite filler was poured into a sealed container.

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The following materials were used to implement the method of the present invention:

[0031] – Highly dispersed silica A300;

[0032] – Catalysts that can be used to prepare carbon nanotubes:

[0033] Composite oxide Fe2O3–MoO3–Al2O3, atomic ratio Fe:Mo:Al=1:(0.04–0.21):(1-3);

[0034] – Argon, in accordance with DSTU GOST 10157:2019 standard;

[0035] – Hydrogen, in accordance with DSTU 2655-94;

[0036] – Ethylene, in accordance with DSTU ISO 8174:2005;

[0037] – Propylene, in accordance with DSTU ISO 8563:2012;

[0038] – ethanol, in accordance with DSTU GOST 10748.1...14:2008;

[0039] – Carbon nanotubes, in accordance with TUU 24.1-03291669-009:2009 standard;

[0040] – Acrylonitrile butadiene copolymer NBR 3365;

[0041] – Industrial zinc oxide (vulcanizing agent);

[0042] – Stearic acid ASTM 1801;

[0043] – Antioxidant ASTM IPPD (N-isopropyl-N'-phenyl-p-phenylenediamine);

[0044] – Internal release agent ASTM 935P;

[0045] – Plasticizer DOP;

[0046] – Rheometer

[0047] – Sulfur powder (brand: Sigma-Aldrich), purity 98.5%;

[0048] – Accelerator N-cyclohexyl-2-benzothiazole sulfenamide (CBS);

[0049] –Accelerator tetramethylthiuram disulfide (TMTD);

[0050] – Reactors for the preparation of composite fillers;

[0051] – Banbury Z-type mixer;

[0052] – Bridge two-roll mixer;

[0053] – Heat press;

[0054] –Ultrasonic mixer UZDN-M900T;

[0055] – Planetary mixer Waring 8.8A012;

[0056] – Tensile testing machine 2167P50;

[0057] – Tensile testing machine Testometric MT350.

[0058] Example 1

[0059] The catalyst Fe2O3–MoO3–Al2O3 (atomic ratio of Fe:Mo:Al=1:0.04:3) and highly dispersed silica (10 g in total) were taken in a Waring 8.8A012 planetary mixer and stirred for 4 minutes. The mixture was then placed in a rotary reactor and stirred at an argon flow rate of 400-450 cm 3 Heat to 680°C at 400 °C / min, hold for 5 min, then reduce the argon flow rate to 40-45 cm 3 / min, ethylene (400cm 3 / min) and hydrogen (200cm 3 / min) of mixed gas. After 30 minutes, the mixed gas was stopped, the heating device was turned off, the reactor was purged with argon, and the obtained composite filler was poured into a sealed container. The mass of the product was 47 grams, the mass of the multi-walled carbon nanotubes was 40 grams, and the mass of the highly dispersed silica and the oxide catalyst residue was 7 grams. The details are shown in Table 1.

[0060] To verify the technical effect achieved, laboratory rubber samples were prepared based on the prototype and the composite filler of the present invention. 100 grams of acrylonitrile-butadiene copolymer NBR 3365 were loaded into a Banbury Z-type mixer, and 5.0 grams of industrial zinc oxide, 1.5 grams of stearic acid, 2.0 grams of IPPD antioxidant, 1.0 grams of internal mold release agent ASTM 935P and 0.05 grams of sulfur powder were added and stirred. Stirring was continued for 4-6 minutes. Then 3 grams of the prepared composite filler and 10 grams of plasticizer DOP were added, and stirring was continued for 2-5 minutes. The resulting mixture was poured out and cooled to below 110°C. Then 1.5 grams of accelerator CBS (N-cyclohexyl-2-benzothiazole sulfonamide) and 2.0 grams of accelerator (tetramethylthiuram disulfide) were added to an open double-roll mixer and stirred until uniform. The resulting mixture was placed at room temperature for 24 hours and then vulcanized at 140-160°C and a pressure of 12-18MPa. The vulcanization used a sample mold suitable for measuring the mechanical properties of the obtained rubber composition. The prepared samples were used to measure tensile strength, breaking strain, 100% elongation stress, 200% elongation stress, and Shore hardness. The performance test results are shown in Table 2.

[0061] Example 2

[0062] Take the catalyst Fe2O3-MoO3-Al2O3, the atomic ratio is Fe:Mo:Al=1:0.21:1), the mass ratio of the catalyst to the highly dispersed silica is 1:1; then proceed according to the method described in Example 1, except that the mass ratio of the catalyst to the highly dispersed silica is changed. The specific details are shown in Table 1 and Table 2

[0063] Embodiment 3-6

[0064] The catalyst Fe2O3-MoO3-Al2O3 is the same as that in Example 1, except that the mass ratio of the catalyst to the highly dispersed silica is changed. The rest is the same as that in Example 1, as shown in Tables 1 and 2.

[0065] Comparative Example 1

[0066] Prototype Example 7n, which does not contain the filler of the present invention ((adding highly dispersed silica and multi-walled carbon nanotube equivalent fillers) equivalent to Example 1), is prepared as follows: 100 grams of acrylonitrile-butadiene copolymer NBR 3365 is loaded into a Banbury Z-type mixer, and 5.0 grams of industrial zinc oxide, 1.5 grams of stearic acid, 2.0 grams of IPPD antioxidant, 1.0 grams of internal mold release agent ASTM935P and 0.05 grams of sulfur powder are added and stirred. Stirring is continued for 4-6 minutes; then 0.4 grams of highly dispersed silica and 2.6 grams of multi-walled carbon nanotubes and 10 grams of plasticizer DOP are added, and stirring is continued for 2-5 minutes. The resulting mixture is poured out and cooled to below 110°C. Then 1.5 grams of accelerator CBS (N-cyclohexyl-2-benzothiazole sulfonamide) and 2.0 grams of accelerator (tetramethylthiuram disulfide) are added to an open double-roll mixer and stirred until uniform. The resulting mixture was placed at room temperature for 24 hours and then vulcanized at 140-160°C and a pressure of 12-18 MPa. The vulcanization used a sample mold suitable for measuring the mechanical properties of the resulting rubber composition. The prepared samples were used to determine tensile strength, breaking strain, 100% elongation stress, 200% elongation stress, and Shore hardness. The performance test results are shown in Table 2.

[0067] Comparative Example 2

[0068] Prototype Example 8n, which does not contain the filler of the present invention ((adding highly dispersed silica and multi-walled carbon nanotube equivalent fillers) is equivalent to Example 5), and the preparation method is as follows: 100 grams of acrylonitrile-butadiene copolymer NBR 3365 is loaded into a Banbury Z-type mixer, and 5.0 grams of industrial zinc oxide, 1.5 grams of stearic acid, 2.0 grams of IPPD antioxidant, 1.0 grams of internal mold release agent ASTM935P and 0.05 grams of sulfur powder are added and stirred. Continue stirring for 4-6 minutes; then add 8 grams of highly dispersed silica and 10 grams of multi-walled carbon nanotubes and 10 grams of plasticizer DOP, and continue stirring for 2-5 minutes. The resulting mixture is poured out and cooled to below 110°C. Then add 1.5 grams of accelerator CBS (N-cyclohexyl-2-benzothiazole sulfonamide) and 2.0 grams of accelerator (tetramethylthiuram disulfide) to an open double-roll mixer and stir until uniform. The resulting mixture was placed at room temperature for 24 hours and then vulcanized at 140-160°C and a pressure of 12-18 MPa. The vulcanization used a sample mold suitable for measuring the mechanical properties of the resulting rubber composition. The prepared samples were used to determine tensile strength, breaking strain, 100% elongation stress, 200% elongation stress, and Shore hardness. The performance test results are shown in Table 2.

[0069] Test Case

[0070] Table 1 shows the mass ratio of the catalyst to the highly dispersed silica in Examples 1-6, and the preparation parameters of the filler in each Example.

[0071] Table 1. Parameters of the method for preparing composite fillers

[0072]

[0073] Table 2 shows the composition [parts by weight per 100 parts by weight of rubber (phr)] and properties of a rubber composition based on acrylonitrile-butadiene copolymer NBR 3365.

[0074] Table 2. Composition and properties of rubber compositions

[0075]

[0076] From the data listed in Table 2, we can conclude that the present invention achieves the following technical effects: a) Compared with Example 7n. (total filler value is 3phr) prepared according to the prototype, the tensile strength of Example 1 (3phr filler) increased by 0.2MPa, the breaking strain increased by 10%, the 100% tensile stress (ε100%) increased by 0.1MPa, the 200% tensile stress (ε200%) increased by 0.2MPa, and the Shore hardness also increased by 2 degrees.

[0077] b) Compared with Example 8n. (total filler value is 18 phr) prepared according to the prototype, the tensile strength of Example 5 (18 phr filler) increased by 3.0 MPa, the breaking strain increased by 15%, the 100% tensile stress (ε100%) increased by 0.2 MPa, the 200% tensile stress (ε200%) increased by 0.2 MPa, and the Shore hardness also increased by 3 degrees.

[0078] We can also see an unexpected result from Table 2. When the composite filler is 3-19phr, its mechanical properties gradually increase, but when it reaches 20phr, the performance drops off sharply. It is speculated that this is because too much composite material is added and reaches a threshold, causing the performance to drop sharply. This shows that there is an optimal range for the content of composite fillers. When this range is exceeded, the performance may drop sharply due to uneven dispersion or other factors caused by excessive fillers.

[0079] In summary, the above embodiments and test examples show that the present invention combines highly dispersed silica with a composite oxide catalyst to prepare a composite filler combined with highly dispersed silica and carbon nanotubes. This method significantly improves the uniform distribution of the filler in the rubber, solves the problem of uneven filler distribution in the prior art, and can more significantly improve the mechanical properties of the rubber at the same filler content.

[0080] The above are only a few preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite filler, characterized in that: The following steps are involved: 1) mixing highly dispersed silicon dioxide and a composite oxide catalyst for preparing carbon nanotubes in a mass ratio of 1:1 to 85:1; the composite oxide catalyst is Fe2O3-MoO3-Al2O3, and its atomic ratio is Fe:Mo:Al=1:(0.04-0.21):(1-3); 2) The mixed materials are fed into a reactor, and the mixed materials are sprayed into a mixed gas consisting of hydrogen, ethylene or propylene, and carrier gas argon at a temperature of 650°C-700°C to react; 3) After the reaction is completed, the introduction of the mixed gas is stopped, the heating device is turned off, and the reactor is purged with argon to obtain a composite filler.

2. The method for preparing a composite filler according to claim 1, characterized in that: The reaction time of the mixed material in the step 2) in the reactor is 20-60 minutes.

3. The method for preparing a composite filler according to claim 1, characterized in that: The step 2) further comprises the step of stirring the mixed material in a planetary mixer for 5-10 minutes before feeding the mixed material into the reactor.

4. The method for preparing a composite filler according to claim 1, characterized in that: The reactor in step 2) is a cylindrical quartz reactor, which is driven by electricity to rotate at a speed of 60-90 rpm, and the rotation axis of the reactor is inclined at 8° to the horizontal plane.

5. The method for preparing a composite filler according to claim 1, characterized in that: In the step 2), during the reaction process, argon is first introduced to make the pressure in the reactor reach a predetermined value, and then the mixed material is sprayed into the reactor, and then the flow rate of argon is adjusted, and a mixed gas of hydrogen, ethylene or propylene is introduced.

6. The method for preparing a composite filler according to claim 5, characterized in that: The predetermined value is 400-450cm 3 / min argon flow rate.

7. The method for preparing a composite filler according to claim 6, characterized in that: During the reaction, the flow rate of the mixed gas of hydrogen, ethylene or propylene was 400 cm 3 / min, the flow rate of argon carrier gas was 400 cm 3 / min.

8. A composite filler, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. Use of the preparation method according to any one of claims 1 to 7 or the composite filler according to claim 8 in the preparation of rubber.

10. A rubber product, characterized in that: Prepared by the following steps: a. Load 80-120 parts of acrylonitrile-butadiene copolymer NBR 3365 into a Banbury Z-type mixer, add 3-8 parts of industrial zinc oxide, 1-2 parts of stearic acid, 1-3 parts of IPPD antioxidant, 0.5-1.5 parts of internal release agent ASTM 935P and 0.03-0.08 parts of sulfur powder, and continue stirring for 4-6 minutes; b. Add 1-5 parts of the prepared composite filler and 5-15 parts of plasticizer DOP, and continue stirring for 2-5 minutes; c. Pour out the obtained mixture and cool it to below 110°C, then add 1-2 parts of accelerator CBS (N-cyclohexyl-2-benzothiazole sulfenamide) and 1-3 parts of accelerator (tetramethylthiuram disulfide) into an open double-roll mixer and stir until uniform; d. Place the resulting mixture at room temperature for 12-36 hours and then vulcanize it at 140-160°C and a pressure of 12-18 MPa.